Sport Performance Profile in Men`s European Modern Handball: Discriminant Analysis between Winners and Losers - Antanas Skarbalius; Kazimieras Pukėnas; Gabija Vidūnaitė (Lithuanian Sports University, 2018)
Research background and hypothesis. Europeans have won Olympic and world gold medals since modern indoor men's handball became an international sport (1938) and an Olympic sport (1972) (www. ihf.com). Nevertheless, no research has been carried out in order to find out the tendencies in European modern men's handball. Research aim of this study was to illustrate discriminant indicators of sport performance between winners and losers in European men's modern handball match activities. Research methods. Data sets were gathered from the European Handball Federation (EHF) website (http:// www.eurohandball.com) covering the five European Men's Handball Championships (EMHC): 2002, 2004, 2006, 2008 and 2010 (n = 239 matches). Each match was classified as successful and non-successful for each team, and then the number of analysed matches doubled to 478. We examined 28 variables of sport performance, but only 15 key indicators where significant discriminant between winners and losers at least in one EMHC was shown. Research results. Winners scored more goals (p < 0.01, p < 0.001), were better in total attack (p < 0.001) and positional attack (p < 0.01, p < 0.001), performed more efficiently in shooting total (p  < 0.001) and shooting from long distance (p < 0.01, p < 0.05), and goalkeepers saved more throws (p < 0.05, p < 0.001). Discussion and conclusions. Winning and losing teams played in the same pattern (p > 0.05). In many cases the  separate match-play was determined by using temporal model of playing style. The phenomenon is that teams scored more goals in the second half than in the first one despite the fact that players' activities decreased in the second half.  Sport performance profile in European modern handball can generate a useful database. Keywords: sports games, performance analysis, elite athletes.